VALIDITY AND RELIABILITY TEST FOR INDEPENDENCE STUDENT SCHOOL BASE CLASS 6 - Dwi Suratimah, Ardiana; Suratimah , Dwi (Schola, 2023)
Every research project needs a tool to gather data using. The validity and reliability criteria must be followed while preparing test and non-test data. It is feasible to confirm the data's consistency and correctness using SPSS software. This research project will outline the phases of learning evaluation courses in the validity and reliability test. Data on student independence surveys were taken at several primary schools, including SDN Srondol Kulon 03 and SDN Srondol Kulon 02. The instrument's preparation findings were used for this purpose. If the count of r is more than the table of r, then the validity test is valid. This means that out of a total of ten things, six are valid, seven are comments about food parenting, eight are statements about psychosocial parenting, and seven are statements about hygiene parenting. Additionally, with relation to healthcare, three out of the six assertions are applicable to parents. If the reliability test has a Cronbach's alpha better than 0.6 or the r-table, then it is considered reliable. Every single statement question in this survey that passed the reliability test yielded reliable data.